Student Management Before, During, and After the Covid-19 Pandemic at MI Al-Wahdah Sardonoharjo - Nudin, Burhan; Saputra, Ricky Dwi; Akbar, Ilham (AS-SABIQUN, 2023)
When a global pandemic in the form of covid-19 hit the world. The impact was also experienced by the world of education in Indonesia. Many academics, starting from teachers, leaders, students, even parents or guardians of students have to adapt. The aim of the research is to analyze the concept of student management, implementation of student management, and student management of classes. This research was conducted to analyze Student Management Before, During and After the Covid-19 Pandemic at MI Al-Wahdah Sardonoharjo, Kec. Ngaglik, Kab. Sleman. This type of research is field research. This research approach uses a qualitative approach. Data collection techniques using interviews, documentation, and observation. The technique for determining informants used a purposive sampling technique. Informants are the Head of Madrasah, Educational Staff, and Homeroom Teacher. The results of this study include the concept of Education management at MI AL-Wahdah which shows planning, organizing, directing, and supervising the efforts of MI AL-Wahdah to achieve educational goals. Furthermore, the implementation of face-to-face learning prior to the pandemic which was forced to turn into distance learning during the pandemic made MI AL-Wahdah have to follow the new system and adapt even though several obstacles would appear at first. The difference between offline class management before the pandemic and online class during the pandemic was in the form of reduced study hours in online classes and no extracurricular activities during the pandemic.